Hierarchical framework of CoZnS as a high-performance electrode material for supercapacitors. Issue 1 (1st January 2023) - Chavan, G.T.; Sikora, A.; Pawar, R.C.; Warycha, J.; Morankar, P.J.; Jeon, Chan-Wook
Abstract: Efficient renewable energies are needed to meet the energy demands of modernized civilization. Therefore, this study evaluated composite Co1- x Zn x S (0.04 ≤ x ≤ 0.34) (CZS-1 to CZS-6) thin film electrodes produced using a chemical growth approach as effective energy storage devices. Systematic integration of Zn 2+ in the CoS host formed the polycrystalline Co0.24 SZn0.76 (cubic) phase. The electrochemical measurements revealed a high diffusion rate and low series resistance, resulting in an excellent specific capacitance (Cs ) of 1288 F g −1 at a current density of 2 mA cm −2 with better rate performance. In addition, the optimal electrode (CZT-5) showed a better power density of 8.86 kW kg −1 and an energy density of 44.4 Wh kg −1 with excellent capacitive retention (85% after 5000 cycles). The enhanced performance could stem from the spongy rose flower-like nanostructure with a covered network of polygonic petals. Consequently, the replacement of Co 2+ with Zn 2+ also contributed by exchanging the oxidation states of targeted atoms, including Co 2+, Co 3+, Zn 2+, and S 2− . Moreover, surface topographical insight states that crystalline growth of the CZS samples with hillocks and valleys and CZS-5 sample exhibited maximum total roughness.